Family management, family ownership and downsizing: Evidence from S&P 500 firms - Jörn Hendrich Block (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2008)
Little is known about the relationship between family firms and their employees. This paper aims to close this gap. We distinguish between family management and family ownership as two dimensions of family firms and analyze their respective influence on downsizing. Our findings show that family management decreases the likelihood of downsizing, whereas the extent of family ownership decreases the likelihood of downsizing only with regard to deep job cuts (above 6%). We conclude that family managers have a strong long-term perspective, which is in line with both agency and stewardship theory. Yet, the idea that reputation concerns lead family owners to shy away from downsizing is only partially supported.
Keywords: G34; L21; M12; M13; M14; M51; 330; Family firms; family management; family ownership; job cuts; downsizing; layoffs; Familienunternehmen; Eigentümerstruktur; Arbeitsbeziehungen; Personalabbau; USA